2003
DOI: 10.1002/tie.10066
|View full text |Cite
|
Sign up to set email alerts
|

FDI in CEECs: How do Western investors survive?

Abstract: Executive SummaryThis article emphasizes that knowledge transfer across a firm's boundaries, in a transition context, implies a specific involvement of Western investors. They need to promote specific relationships within affiliates. This article emphasizes two points. First, partners have few common practices and do not share the same perception of the firm. This is the problem with building new capabilities. Second, Western firms have to mobilize organizational resources to build efficient affiliates (new hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
1
16
2
Order By: Relevance
“…Thus, when the individuals of the learning organisations (i.e. IJVs) do not possess adequate prerequisites to recognise, value and understand new knowledge and practices, the acquisition of local market information may be difficult (Fabry & Zeghni, 2003). However, our result reveals somewhat different outcome from previous commentaries.…”
Section: The Service Industries Journalcontrasting
confidence: 81%
See 1 more Smart Citation
“…Thus, when the individuals of the learning organisations (i.e. IJVs) do not possess adequate prerequisites to recognise, value and understand new knowledge and practices, the acquisition of local market information may be difficult (Fabry & Zeghni, 2003). However, our result reveals somewhat different outcome from previous commentaries.…”
Section: The Service Industries Journalcontrasting
confidence: 81%
“…The reason why this research has yielded results which are contradictory to the common perception may be found in Fabry and Zeghni (2003). They reveal that employees generally suffer a lack of ability to communicate internally in transitional countries because the former management style is highly hierarchical in those economies.…”
Section: The Service Industries Journalcontrasting
confidence: 60%
“…The institutional context shapes the social meaning of organisational practices and provides them with legitimisation from the society's point of view. For example Fabry and Zeghni (2003) explain that habits of the employees in CEE countries were heavily influenced by the communist system. To change these habits, to create the willingness to acquire new skills, and to improve productivity, Western companies had to be aware of the institutional characteristics.…”
Section: Knowledge Transfer and Motivationmentioning
confidence: 99%
“…Though microentrepreneurs, or entrepreneurs that create and grow microenterprises, may not be the direct recipients of such FDI, the presence of FDI within an emerging market can strengthen financial markets (Chakrabarty, 2009; Goldberg, 2004; Kuroda & Kawai, 2002), and assist social and economic development (Borensztein, De Gregorio, & Lee, 1998; Ozawa, 1992). As a result, a contagion effect of FDI inflow exists such that FDI strengthens the business climate of the emerging market to create knowledge spillovers (Chakrabarty & Whitten, 2011; Fabry & Zeghni, 2003; Whitten, Chakrabarty, & Wakefield, 2010), makes the market more competitive, assists the development of new institutions, and alters markets and systems to be more efficient and effective (Almor, 2011; Chakrabarty & Wang, 2012; Grachev, Rogovsky, & Bobina, 2006). While FDI can result in greater formal/contractual business opportunities in the host country, there are also positive spillovers that arise from “non‐market transactions when resources, notably knowledge, are spread without a contractual relationship” (Meyer, 2004, p. 260).…”
Section: Theory Development and Hypothesesmentioning
confidence: 99%